Mentoring Experiences of New Online Teachers: Voices of Graduate and Early Career Instructors - Heather Garcia; Mary Ellen Dello Stritto (Teaching & Learning Inquiry: The ISSOTL Journal)
This research study explores the mentoring experiences of graduate student and early career instructors who teach online courses at a mid-size public university in the United States. As members of a centralized online learning unit that works with instructors teaching online courses across a range of disciplines, we sought to better understand the mentoring experiences of instructors who are new to online teaching. Using a narrative methodology, we analyzed interview transcripts and found that graduate student and early career instructors have variable access to mentoring, experience different sources of mentoring, and engage with multiple types of mentoring. We found that graduate student instructors have more access to different sources and types of mentoring than early career instructors, but that both groups desired additional mentoring opportunities. Participants recognized the value of mentoring experiences as part of their overall professional development. We conclude with suggested actions for units looking to support mentoring for online instructors.